The relationship of physical activity with nutritional status and body composition in traditional and modern populations in South Sulawesi, Indonesia. - ARRUAN, Wanty; BUKHARI, Agussalim; HANDAYANI, Nevi Dwi; TASLIM, Nurpudji A.; FARADILAH, Andi; AMINUDDIN (Nutrición Clínica y Dietética Hospitalaria, 2024)
Background: Decreased physical activity in modern society, influenced by lifestyle and technology, leads to energy imbalances that impact nutrition, obesity, and body composition issues, which increase the risk of metabolic diseases, such as hypertension, type 2 diabetes, cardiovascular disease, and dyslipidemia. Objective: This study aimed to determine the relationship of physical activity to nutritional status and body composition in traditional and modern populations in South Sulawesi. Methods: This study was an observational study with a cross-sectional approach, which examined the relationship between variables in modern and traditional groups. The study was conducted in Tana Toa Village and Makassar City from February to November 2022. Each group consisted of 50 adults who met the criteria. Data were collected through IPAQ questionnaire and direct measurement for anthropometric data (body weight and body height) and body composition. Data were analysed using SPSS version 26 with t-test analysis. Results: The results showed that the traditional group performed moderate physical activity (56.0%), while the modern group performed low physical activity (58.0%, p = 0.000). BMI and waist circumference had a negative relationship with physical activity, where subjects with overweight-obese BMI tended to be less active (r = -0.298, p = 0.003), and subjects with central obesity performed more low activities (r = -0.403, p = 0.000). Muscle mass had a positive correlation, subjects with normal muscle mass were more active (r = 0.356, p = 0.000). However, the relationship between physical activity and bone mass was not significant (p = 0.111) Conclusion: Physical activity had a significant association with several indicators of nutritional status and body composition. The modern group had low activity with higher body mass index, waist circumference, fat mass and visceral fat compared to the traditional group with higher muscle mass